The Future has arrived: cyborgs, biotechnology and nursing science - Teixeira de Almeida Vieira Monteiro, Ana Paula (2014)
At present, Nursing Science is in the throes of revolutionary change, accelerated and driven by rapid technological innovation and by the globalisation of the health care industry. The aim of this paper is to reflect on the epistemological paradigms of nursing science in a critical perspective related to trends and emerging issues in health care. In this paper we identified and analysed some new trends and emerging paradigms in Nursing Science: knowledge focused on biotechnology; Nursing information technology knowledge; the human body as a cyborg body and the use of aesthetics in nursing practice.